Rising trends in surgery for rotator cuff disease in Western Australia - Thorpe, A.; Hurworth, M.; O'Sullivan, Peter; Mitchell, T.; Smith, Anne (John Wiley & Sons, 2016)
Background: Increasing rates of surgery for rotator cuff disease have been reported in the past decade in a number of countries worldwide. Rising surgery rates do not correspond with equivalent increases in shoulder pain prevalence. The aims of the study were: to investigate trends in population-adjusted surgical rates for rotator cuff disease in Western Australia (WA) from 2001 to 2013; to compare population-adjusted arthroscopic surgical trends between (i) private versus public hospital setting; (ii) sex and (iii) different age groups; and to evaluate rising health care costs associated with arthroscopic surgical rates for rotator cuff disease. Methods: Numbers and costs for surgical procedures for rotator cuff disease performed in WA were extracted from the WA Department of Health database for the 13-year period, 2001–2013. Results: Rising surgical trends were demonstrated with arthroscopic subacromial decompression (ASAD) and arthroscopic reconstruction showing large proportional increases of 108.7 and 68.4%, respectively. Increasing trends were mostly linear across private and public hospital settings, gender groups and different age groups. The rise in consumer price index-adjusted costs for ASAD in private and public hospitals was 273.7 and 320.8%, respectively, and for arthroscopic reconstruction 220.2 and 472.5%, respectively. Conclusion: The substantial increase in arthroscopic surgery rates for rotator cuff disease and associated costs in WA over the period 2001–2013 is in spite of evidence that surgical outcomes are no different to exercise interventions. Conservative treatments should be recommended as an initial treatment choice, to arrest escalating health care costs.